Managing harvesting for forest sustainability in Malaysia : an SFL perspective - Wan Farah Wani Wan Fakhruddin; Zuraidah Mohd Don; Hanita Hassan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Forest management practices have been addressed widely in the forestry discipline but are rarely considered from a linguistic perspective. Linguistic exploration of the construction of meaning in forest discourses helps provide greater detail on how forest resources are governed through the forest management practices carried out by forestry professionals. This study adopted the approach from Systemic Functional Linguistics (SFL) and Halliday’s Introduction to Functional Grammar to examine how lexicogrammatical resources are used by forestry professionals to institutionalise their narrative on sustainable forest management practices. Six field inspection reports issued by the Forestry Department of Peninsular Malaysia were selected as data for analysis. The reports were examined as a genre to ascertain their generic structure and the elements they contained. The findings show that the reports provide essential information concerning various aspects of forest management best practices, including technical information of the forest areas, their geographical and topographical conditions within and around the areas, the distribution of tree stands and other equally important aspects including their environmental, socio-economic and economic values. This paper suggests that a linguistic orientation employed in uncovering forestry matters such as the field inspection report allows concrete evidence of how forest managementpractices are communicated, especially in written reports and whether these practices are aptly represented through their language use.